Conflict in Amanah Saham Berhad (ASB) - Izham, Nur Aqilah; Kayadibi, Saim (IIUM Press, 2011)
We are pleased to do the assignment that related to the fiqh in finance or business. Then, we choose to do about the transaction of Amanah Saham Nasional Berhad (AS~B). Amanah Saham Nasional Berhad (ASNB) was established on May 22, 1979, to manage the unit trust funds launched by PNB. Having been in the industry for more than 25 years, ASNB has confinns to maintain its position as a leading unit trust manager, controlling more than 40% of the total units in circulation. ASNB is wholly-owned by Pennodalan Nasional Berhad (PNB)